Transient Cooling of Waxy Crude Oil in a Floating Roof Tank - Jian Zhao; Yang Liu; LiXin Wei; Hang Dong (Journal of Applied Mathematics)
The transient cooling of waxy crude oil stored in a floating roof tank located in alpine region is studied by means of numerical simulation, accomplished with a two-dimensional model in cylindrical coordinates with the finite volumes method. The typical evolution of transient natural convection and temperature distribution is investigated which can be divided into four stages. For the transient natural convection, it is concluded as the formation, expansion, degradation, and vanishing stage, along with it is the evolution of temperature field regarded as the local cooling, integral cooling, the thermal stratification, and heat conduction course. Special attention is given to the solidified process of waxy oil and its influence on the cooling process of crude oil. Moreover, the effect of tank size, the temperature gradient between oil and ambient, viscosity, and Cp of waxy crude oil on the cooling rate is investigated. The main characteristic of cooling process obtained from numerical results shows a good agreement with the temperature test results from a large floating tank in the oil depot.